Pemanfaatan Virtual Reality dalam Edukasi Spinal Anestesi Guna Mengurangi Sensasi Nyeri pada Pasien Benign Prostatic Hyperplasia di RSUD Cilacap - Ade Dwi Aulia; Magenda Bisma Yudha; Made Suandika (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
Patients with Benign Prostatic Hyperplasia (BPH) who are scheduled to undergo spinal anesthesia often have limited understanding of the anesthesia procedure and may experience pain and anxiety before surgery. These conditions can affect patient readiness and the perioperative care process. One educational method that can be utilized is Virtual Reality (VR), an interactive audiovisual medium that provides information in a more engaging and understandable way while also serving as a distraction technique to reduce pain perception. This Community Service Program aimed to implement VR as a preoperative educational tool to improve knowledge and reduce pain among BPH patients undergoing spinal anesthesia.The program was conducted by identifying eligible participants, administering a knowledge pre-test and pain assessment using the Visual Analog Scale (VAS), providing spinal anesthesia education through a 3–4 minute VR video, followed by a question-and-answer session, and then conducting a post-test and reassessment of pain levels. The results demonstrated an increase in participants’ knowledge and a reduction in pain following the VR intervention. Before the intervention, most participants had poor knowledge 13 respondents; 65% and moderate pain 11 respondents; 55%. After the intervention, good knowledge increased to 11 respondents 55%, while mild pain increased to 12 respondents 60%. A total of 19 respondents 95% showed improved knowledge, and 17 respondents (85%) experienced pain reduction. The implementation of VR was found to be effective as a preoperative educational medium for BPH patients undergoing spinal anesthesia.